SOCIETY OF RISK AND THE PUNITIVE MESSAGE: an analysis about the recent judicial activism in Brazil as proposal for fear of contention - Freitas Perdigão Lima, Viviane; Cardoso de Jesus, Thiago Allisson (Universidade de Brasília, 2019)
The paper, starting from judicial activism in Brazil in risk society, analyzes the Criminal Law as a formal mechanism to control sources of danger. Reflects performance of the criminal judge and its management in society whose sense of insecurity causes the collective fear. They analyze the criminal law in the risk society and the proactive role of the judiciary on the need for punitive message. The theoretical framework is based on judicial activism to replace public policies of the Legislative or Executive Power by the Judiciary (Baum, 1987) within the risk society, that is, developed in the middle of a chain of economic, political, scientific and which changed the scenario of the conditions of life in this society, thus creating a new criminal law based on a formal mechanism for controlling the various sources of danger of systemic origin (Buergo, 2001). Methodologically, it focuses on judicial activism and risk society. It appears that a new Criminal Law founded on the Constitutional State of Law is legitimate at the present moment, as long as it is committed to constitutional values and usurps the powers of other Powers.